Integrasi Elemen Fun–Playful dan Science-Based Futuristic Design dalam Perancangan Ruang Anak Belajar Sains dan Teknologi - Nur Hadiyatun Nabawi; Husnul Masyitoh (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
This study develops an architectural design framework integrating fun and playful spatial characteristics with futuristic, science-based approaches to enhance children’s engagement with science and technology learning. Traditional learning environments are often rigid and fail to stimulate curiosity, especially among children aged 7–11. Utilizing a qualitative conceptual analysis, this research synthesizes architectural theory, neuroscience learning principles, children’s spatial psychology, and science-based design methodologies. The results show that playful spatial elements—dynamic forms, color contrasts, sensory interactions, and imaginative environments—significantly improve motivation, exploration, and conceptual understanding. Futuristic design components further support scientific literacy by projecting technological possibilities and integrating interactive digital tools. The study produces a conceptual architectural model linking playfulness, scientific experience, and future-oriented visualization. It concludes that learning environments must be intentionally designed to merge emotional engagement, cognitive stimulation, and technological representation. The implications extend to the design of children’s museums, science centers, and early STEM learning facilities.